Comparative case study of evolutionary insights and floral complexity in key early-diverging eudicot Ranunculales models - Sharma, Bharti; Pandher, Mankirat Kaur; Alcaraz Echeveste, Ana Quetzali; Bravo, Marianellie; Romo, Rene Kenny; Ramirez, Sarah Christine (Frontiers in Plant Science, 2024)
Famously referred to as "Darwin's abominable mystery," the rapid diversification of angiosperms over the last ~140 million years presents a fascinating enigma. This diversification is underpinned by complex genetic pathways that evolve and rewire to produce diverse and sometimes novel floral forms. Morphological innovations in flowers are shaped not only by genetics but also by evolutionary constraints and ecological dynamics. The importance of model organisms in addressing the long-standing scientific questions related to diverse floral forms cannot be overstated. In plant biology, Arabidopsis thaliana, a core eudicot, has emerged as a premier model system, with its genome being the first plant genome to be fully sequenced. Similarly, model systems derived from crop plants such as Oryza sativa (rice) and Zea mays (maize) have been invaluable, particularly for crop improvement. However, despite their substantial utility, these model systems have limitations, especially when it comes to exploring the evolution of diverse and novel floral forms. The order Ranunculales is the earliest-diverging lineage of eudicots, situated phylogenetically between core eudicots and monocots. This group is characterized by its exceptional floral diversity, showcasing a wide range of floral morphologies and adaptations that offer valuable insights into the evolutionary processes of flowering plants. Over the past two decades, the development of at least five model systems including, Aquilegia, Thalictrum, Nigella, Delphinium and Eschscholzia within the Ranunculales order has significantly advanced our understanding of floral evolution. This review highlights the conservation and divergence of floral organ identity programs observed among these models and discusses their importance in advancing research within the field. The review also delves into elaborate petal morphology observed in Aquilegia, Nigella, and Delphinium genera, and further discusses the contributions, limitations, and future research directions for Ranunculales model systems. Integrating these diverse models from the early-diverging eudicot order has enhanced our understanding of the complex evolutionary pathways that shape floral diversity in angiosperms, bridging the knowledge gaps essential for a comprehensive understanding of floral evolution.